Le Média – A Populist Critique of Journalists and the Media by Journalists: Journalism as a social good of the people - Tant, Cédric (Brazilian journalism research, 2021)
ABSTRACT – This paper aims to question the critique of journalists and the media by Le Média, a French press body close to a populist party (La France insoumise), which means regularly opposing “the people” and “the elites” (De Cleen & Stavrakakis, 2017; De Cleen, 2019). Through a methodology inspired by the sociolinguistics of Gee (2014) and by the concept of “social goods”, the results bring to light: a metajournalistic critique based on the opposition between “the people” and “the elites”, a desire to delegitimize legacy media and the wish to make journalism a “social good” in the service of “the people”. RÉSUMÉ – Cette recherche vise à interroger la critique des journalistes et des médias par Le Média, un organe de presse français proche d’un parti populiste (La France insoumise), c’est-à-dire qui met régulièrement en avant l’opposition entre le “peuple” et les “élites” (De Cleen & Stavrakakis, 2017; De Cleen, 2019). Plus particulièrement, à travers une méthodologie inspirée de la sociolinguistique de Gee (2014) et notamment du concept de “social goods”, ce travail met au jour une critique métajournalistique, basée sur l’opposition entre le peuple et les élites, qui, tout en délégitimant les médias traditionnels, pose le journalisme en véritable “bien social” au service du peuple. RESUMO – Esta pesquisa busca questionar a crítica sobre os jornalistas e a mídia feitas por Le Média, um veículo da imprensa francesa próximo a um partido populista (La France insoumise), ou seja, que destaca regularmente a oposição entre o “povo” e as “elites” (De Cleen & Stavrakakis, 2017; De Cleen, 2019). De forma mais específica, por meio de uma metodologia inspirada na sociolinguística de Gee (2014) e, particularmente, no conceito de “social goods”, a pesquisa atualiza uma crítica metajornalística, baseada na oposição entre povo e elites, que, ao mesmo em que deslegitimam as mídias tradicionais, definem o jornalismo como um verdadeiro “bem social” a serviço do povo. RESUMEN – Este estudio tiene como objetivo interrogar la critica de los periodistas y de los medios por Le Média, una entidad de prensa francesa cercana al partido populista (La France insoumise), es decir que destaca a menudo la oposición entre el “pueblo” y las “elites” (De Cleen & Stavrakakis, 2017; De Cleen, 2019). Y más específicamente, a través de una metodología inspirada de la sociolingüística de Gee (2014) y del concepto de “social goods” que pone al dia una critica metaperiodista, basado en la oposición entre el pueblo y las élites que, al tiempo que deslegitima los medios tradicionales, plantea al periodismo como un verdadero “social good” al servicio del pueblo.